Customer-Contact Employee Support and Service Recovery Efforts - Younhee Moon (Asia Marketing Journal (Online), 2018)
The purpose of this research is to investigate the effect of customer-contact employees support on service recovery efforts. Service companies should try to prevent the service failure situation from occurring, but it is realistic that the service failure occurs due to the characteristics of the service. Service recovery efforts of service providers are important because effective responses to service failures can enhance customer satisfaction despite service failures. Social support for customer-contact employees needs to improve service recovery efforts. Specifically, this study focuses on the mediation roles of job burnout and customer orientation in relationship between social support for customer-contact employees and service recovery efforts. Social exchange theory was used as the theoretical underpinning of the research model. Based on reciprocity principle, this paper suppose that support for customer-contact employees and service recovery effort are a kind of social exchange relationship. Social supports for customer-contact employees are categorized into internal and external organization. Internal organization is POS(perceived organizational support) and external organization is customer support. The research model was tested with the data gathered from the flight attendants whose emotional labor intensity was relatively high and the service failure frequently occurred. As a result of analysis, social supports for customer-contact employees classified into organizational support, supervisor support, and customer support are found to have differential impacts on job burnout and customer orientation. It has been found that job burnout of service providers is negatively affecting service recovery efforts. On the other hand, customer orientation of service providers has a positive influence on service recovery efforts. Based on the results of the analysis, we provide practical implications for effective service recovery efforts in service failure situations, and suggest the theoretical implications to explain the process of service recovery effort. Finally, limitations of the study and directions for future research are suggested.